Analisis Kualitas Air Permukaan Rawa Gambut Rasau Bervegetasi Mangrove Di Desa Rantau Panjang Kabupaten Muaro Jambi - Guntar Marolop S; Peppy Herawati (Universitas Batanghari, 2020)
Peat soil is a type of soil that is formed from the accumulation of plant debris which undergoes a decomposition process. This is why peat soil contains high organic matter and is acidic. Peat soils will affect the parameters of a surrounding aquatic ecosystem, such as the Rasau peat swamp ecosystem in the village of Rantau Panjang. Peat swamp water parameters are influenced by substances stored in the peat such as having a low pH, high heavy metal content, and having high TSS, TDS, BOD and COD values. The water parameter of peat swamp with mangrove vegetation is better than that of peat swamp that does not have mangrove vegetation. This can be seen if the peat swamp water parameters are laboratory tested. The physical parameters of water, namely temperature, TDS, DHL, color, and turbidity were lower in the Rasau peat swamp with mangrove vegetation compared to the non-vegetated ones. The chemical parameters of the Rasau peat swamp with high density mangrove vegetation such as higher pH, and lower BOD, COD, and iron (Fe) when compared to peat swamps without mangrove vegetation. However, the physical and chemical parameters of vegetated and non-vegetated peat swamps are still above the PPRI No. 82 of 2001.